Structure aggregation of carbon black in ethylene-propylene diene polymer (eXPRESS Polymer Letters)
The modulus of filled and unfilled Ethylene-propylene diene rubber (EPDM) vulcanizates was used to predict the shape-factor of carbon black aggregation in the polymer. Four types of carbon black that vary in particle size and structure were used in this study. Quadratic curves relating the carbon black volume concentration and the modulus ratio of filled and unfilled rubber vulcanizates were used to adopt the shape factor of certain carbon black type. The shape factor of MT, HAF, SRF and Lampblack were 3, 3.75, 4 and 4.25 respectively. X-ray diffraction technique (XRD) was also used to evaluate the relative size of crystallite on the filler surface to that of the rubber and correlating it to the shape factor of carbon black aggregation in the polymer. Effect of the pH values and structure of carbon blacks used on the shape factor of filler aggregates were also studied. It was found that the shape factor is independent on the particle size while it is dependent on the pH value and structure of carbon black. Also the crystallites size of the filler is proportional to the shape factor.